THE TECHNOLOGY OF USING PEDAGOGICAL TERMS IN PRACTICE ON HISTORICAL APPROACHES - Odilova, Malokhat (Журнал иностранных языков и лингвистики, 2023)
Based on historical approaches, the history of the formation of pedagogical terms and technologies associated with practical use, including problematic assignments, allows students to work actively on the problem. There are technologies such as “Problem-Based Learning”, “Project Technology”, “Quest Game”, “STEAM” which reinforce the knowledge of the studied material, develop the practical application of pedagogical terms in the analysis of problems, and work on solving problems independently contribute to the development of responsibility, independence and communication skills.